When Hope And Tension Collide: A Proposal For The Outline Of Mark - Hendry Ongkowidjojo (VERBUM CHRISTI JURNAL TEOLOGI REFORMED INJILI, 2021)
Through a narrative criticism approach, this article describes how the theme of hope-and-tension form a common thread for the entire Gospel of Mark. Understanding how Mark maintains hope and tension throughout his Gospel will help readers explore Mark's Gospel in a more vivid, integral, and relevant way.